Bypass grafting to the right coronary artery with and without endarterectomy: patency at one year. Issue 5 (November 1985) - Kay, P H; Brooks, N; Magee, P; Sturridge, M F; Walesby, R K; Wright, J E
Abstract : Between January 1979 and December 1981, 142 patients undergoing surgery to the right coronary artery agreed to have repeat coronary arteriography one year later. Thirty patients underwent combined endarterectomy and bypass grafting to the right coronary artery. The patency of these grafts was compared with that of grafts in 69 patients undergoing direct grafting to the right coronary artery and in 43 with grafting to the posterior descending coronary artery. There were two hospital deaths and one late death. No patients developed new inferior Q waves on the electrocardiogram. Repeat coronary arteriography at one year showed that 21 (72%) of the 29 grafts were patent after combined endarterectomy and bypass grafting to the right coronary artery. Sixty three (94%) grafts to the right coronary artery and 40 (93%) grafts to the posterior descending coronary artery were patent at one year. Direct grafts to the right coronary artery or its posterior descending branch had a significantly higher patency rate at one year than grafts to the endarterectomised right coronary artery. Graft patency after the combined procedure correlated with the extent of atherosclerosis in the posterior descending coronary artery. It was not influenced by treatment with platelet antagonists. Endarterectomy of the right coronary artery was most successful when it allowed a single graft to perfuse both the large posterior descending and left ventricular branches.